Membangun Kesadaran Tentang Menjaga Kesehatan Rambut Anak Di Desa Bandar Magodang - Habib Al Ghifari Nasution; Khoirunnisa Lubis; Mutiara Arafah Nasution; Suci Dahlya Narpila (Pusat Riset dan Inovasi Nasional, 2024)
Children's health is an important factor that needs to be considered. A child will feel happier and more confident with a good diet. There are still many residents of Bandar Magodang Village, Serdang Berdagai Regency, North Sumatra, who do not realize how important it is to maintain healthy hair. Increasing awareness about the health of newborn children's hair in Bandar Magodang Village is the aim of this research. Survey and interview approaches were used in this research. The research results show that there are still many people who do not know about safe and reliable child care practices. Apart from that, they ignore how important it is to maintain the health of the younger generation.